Dampak Pemberlakuan Insentif Dan Relaksasi Pajak Pandemi Covid-19 Terhadap Kinerja Keuangan Perusahaan Sektor Energi - Ely Safrinawati, Ersa; Oktafiyani, Melati; Ratnawati, Juli; Purwantoro, Purwantoro (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
The aim of this research was to determine the impact of the implementation of incentives and tax relaxation for the Covid-19 pandemic on financial performance as measured by profitability, output, implications of incentives and tax relaxation, debt capacity, capital stock and employee costs in energy companies listed on the Indonesia Stock Exchange from 2017 to 2022. The population in this research is 66 companies in the energy sector listed on the Indonesia Stock Exchange from 2017 to 2022. The sampling technique used in the research was purposive sampling. The data analysis method used is Paired Sample T-test and Wilcoxon Signed-rank Tesst. The results of the research show that profitability, output and capital stock are different before and after determining incentives and tax relaxation. Meanwhile, there is no difference in tax rates and debt capacity before and after the establishment of incentives and tax relaxation for the Covid-19 pandemic.